Correcting Myopia in Domestic Violence Advocacy: Moving Forward in Lawyering and Law School Clinics - Carey, Camille (Columbia Journal of Gender and Law, 2011)
Lawyers and law school clinics have become myopic in their approach to civil domestic violence lawyering. This article argues that domestic violence lawyering should expand beyond its current focus on family law to move domestic violence law and practice forward. Drawing on theoretical frameworks from criminal law and feminist legal theory, this article proposes a lawyering model that expands individual representation across a wide spectrum of case types while also challenging systems that enable battering or do not support victims in their efforts to secure safety. Holistic representation in family law, public benefits, immigration, housing, mortgage foreclosure, tort, and financial matters, among other substantive areas, better serves domestic violence victims and reveals systemic problems facing victims. By taking a dual approach—broad holistic representation of individual victims combined with law reform efforts directed at systemic issues revealed through broad direct representation—lawyers and law school clinics can move domestic violence advocacy forward.